Spiritual Approach For Hypertension Sufferers in Riverbank Areas - Mahdalena Mahdalena; Mahpolah Mahpolah; Suroto Suroto (Universitas Aisyah Pringsewu, 2022)
Hypertension is categorized as the silent disease, the number always increases every year. Hypertension sufferers can experience anxiety which has an impact on their psychological well-being. In a mood of sadness, fear and anxiety, religiosity and spirituality become a guide to life, religious practices become daily activities.Spiritual well-being or spiritual well-being is one of the factors that shows how a person can deal with problems and stress in their life, such as degenerative diseases and other problems that arise. This research aims to explore the spiritual approach of hypertension sufferers using a cross-sectional method in communities along the Martapura river. The results obtained show the spiritual approach of the people along the Martapura river. Very good at controlling emotions and anxiety in dealing with hypertension problems. Society establishes a vertical relationship with GodJust as building religious rituals is very well established, so are horizontal relationships with fellow creatures (man and the universe). A spiritual approach is of particular concern in treating hypertensive patients.